Optimasi Komposisi Pakan Ternak Sapi Menggunakan Algoritme Genetika - Simulated Annealing - Akhmad Syururi; Nurul Hidayat; Ratih Kartika Dewi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Beef consumption in Indonesia keeps increasing, but the increase has not been balanced with the addition of an adequate production. The rate of population increase beef cattle is relatively slow, 4.23% in 2007. The productivity of the livestock affected by the feed factors, management and breeding. The problem often encountered breeders is the availability of feed, which feed given to livestock contain nutrients that are low so will affect the availability of feed and digestibility of nutrients that impact low produkt ivitas cattle. Based on cases occurs, then the system is built on this research is "beef cattle feed composition optimization using genetic algorithm and simulated annealing". Methods used in beef cattle feed composition optimization on this system using a genetic algorithm and simulated annealing. The purpose of merging algorithm and genetic simulated annealing (SA) is to make use of the advantages of simulated annealing that are able to survive are facing local optimum and the search process which is controlled by the temperature to be used in cover lack of genetic algorithms. The results of the testing that has been done progressively smaller values popsize and iterations, the greater the value of tn and t0 then the more likely genetic algorithm and simulated annealing to get better results than the algorithm Genetics alone, otherwise the larger value of popsize and iterations, the smaller value of tn and t0 the small possibility of genetic algorithm and simulated annealing for getting better results., genetic algorithm, simulated annealing